Transmembrane-4-L-six-family-1, a potential predictor for poor prognosis, overexpressed in human glioma. Issue 8 (27th May 2015) - Wang, Peng; Bao, Wenjuan; Zhang, Guoliang; Cui, Huixian; Shi, Geming
Abstract : Transmembrane-4-L-six-family-1 (TM4SF1), a tumor-associated antigen, is expressed in various human epithelial malignancies including breast, ovarian, lung, and colon carcinomas. The aim of the present study was to measure TM4SF1 gene expression in human glioma tissues and to investigate its relationship with patient outcome. We measured TM4SF1 expression in tumor tissue from 72 patients with glioma and in eight control brain tissues by means of quantitative reverse transcription-PCR, western blotting, and immunohistochemistry. The survival data including age, sex, Karnofsky performance scores, epilepsy, size of tumor, extent of resection, pathological grade, and TM4SF1 expression were analyzed using Kaplan–Meier analysis and the multivariate test method (Cox's proportional hazards model). We observed a higher level of TM4SF1 expression in human glioma tissues than in control brain tissues. Furthermore, TM4SF1 expression increased with ascending tumor grade ( r s =0.950, P <0.05). Kaplan–Meier analysis with the log-rank test indicated that high TM4SF1 expression had a significant negative impact on overall survival ( P <0.001). Moreover, multivariate Cox regression analysis revealed that TM4SF1 was an independent prognostic marker in glioma patients. These findings indicate that (a) TM4SF1 is overexpressed in human gliomas in general and (b) the precise level of expression might predict outcome and could be of clinical value.